307 Clinical Efficacy of Thrombolytic Therapies in Mothership Versus Drip and Ship Model: A Systematic Review and Meta-Analysis. (April 2023) - Mohamed, Ahmed; Fatima, Nida; Altahou, Abraham; Ahmed, Ayman; Shuaib, Ashfaq; Saqqur, Maher
Abstract : INTRODUCTION: There exist substantial uncertainty in understanding the benefit of organizational paradigms in stroke centers. METHODS: Studies between 1990 and 2021 were analyzed from electronic databases. Critical time measurements, functional independence, and mortality were all compared. IBM SPSS 23 and Rev Manager were used for statistical analysis. RESULTS: 7, 232 patients' data were collected from 24 studies. MT+IVtPA vs. IVtPA only did not show significant difference between both cohorts when analyzing NIHSS (p = 0.461). When conducting a subgroup analysis to interpret differences between MS and DS patients in each treatment method, no significant difference (p > 0.05) was noted for the mean time of symptoms to onset and the mean stroke onset to successful recanalization time for the Mt+IVtPA (p = 0.267) and IVtPA cohorts (p = 0.461). The MT+/-IVtPA reported significant differences between MS and DS patients in both these times (p < 0.001 and p = 0.011, respectively). Moreover, no significant difference was noted for mortality at 90-days and symptomatic intracranial hemorrhage (sICH) among these different thrombolytic groups for the DS and MS model patients in all three treatment method cohorts (p = 0.941 for the MT+IVtPA group, p = 0.993 for the MT+/-ItPA and N/A for IVtPA only). The MT+/-IVtPA cohort was the only one to show a significantly larger percentage of patients in the DS group, compared to the MS, to have a mRS score of 3-6 (bad functional outcome) (p = 0.034). CONCLUSIONS: Our results showed that there is no sufficient significant difference in clinical efficacy based on MS or DS models in each treatment type.